The synergistic effect of carbon performance and technological innovation on corporate financial performance - Yan, Jin; Zhou, Hui; Mu, Jialin; Zhang, Ying; Rahman, Airin (Frontiers in Psychology, 2022)
In order to further implement the goal of “dual carbon” proposed by China’s government, and promote energy enterprises to carry out low-carbon economic transformation, this paper takes listed companies in China’s A-share energy industry from 2014 to 2019 as samples to conduct descriptive statistics, correlation test and regression analysis, and empirically studies the impact of carbon performance and technological innovation on financial performance of China’s energy industry as well as their roles under different property rights. At the same time, the variables were delayed for one period to investigate the sustainability of carbon performance and technological innovation on financial performance and to weaken the endogeneity of the reverse causality between financial performance, carbon performance and technological innovation. The results show that good carbon performance and technological innovation in the energy industry can positively affect the financial performance of enterprises. During the research of interactive relationship, we find that carbon performance and technological innovation have synergistic effect on energy firm’s financial performance, which means technology innovation can significantly positive to adjust the action of carbon performance on financial performance,and carbon performance at the same time can also be positive to adjust the action of technology innovation on financial performance. They mutually promote energy enterprise’s financial performance. Further experimental research among different property- rights-owned enterprises, we found that the synergistic effects of carbon performance and technological innovation on corporate financial performance is much more significant in non-state-owned enterprises, possibly due to private firms’ capital profit-seeking nature. The results will guide and inspire China’s energy enterprises’ low carbon development strategy formulation and implementation under the background of “dual carbon” goal.